Role of Mast Cells in the Control of Aldosterone Secretion - Lopez, Antoine-Guy; Duparc, Céline; Naccache, Alexandre; Castanet, Mireille; Lefebvre, Hervé; Louiset, Estelle (Hormone and Metabolic Research, 2020)
Mast cells are immune cells present in adrenals from various species. Proliferation and activation of adrenal mast cells seem to be influenced by environment, since they increase during summer and in response to sodium restriction in frogs and mouse, respectively. Although the physiological factors regulating adrenal mast cell activity have not been identified, they might involve neurotransmitters and the renin-angiotensin system. Some data indicate that adrenal mast cells stimulate proliferation of steroidogenic cells in the zona glomerulosa and activate the mineralocorticoid production. In human, mast cell degranulation stimulates aldosterone synthesis through the release of serotonin (5-HT) and activation of 5-HT4 receptors. Increase in mast cell population and upregulation of the 5-HT signaling pathway occur in aldosterone-producing adenomas. In particular, aldosterone-producing adenoma cells overexpress 5-HT4 receptors and are hyper-responsive to 5-HT4 receptor agonists. These data suggest that the intra-adrenal serotonergic regulatory system represents a potential target for development of both adrenal imaging methods to evaluate the lateralization of aldosterone production, and pharmacological treatments of primary aldosteronism.
Keywords: adrenal cortex; aldosterone; aldosterone-producing adenoma; mast cells; serotonin